2018
DOI: 10.1007/s10578-018-0821-9
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Neural Responses to Emotionally Valenced Facial Stimuli: A Potential Biomarker for Unemotional Traits in Early Childhood

Abstract: Callous-unemotional (CU) traits are characterized by deficits in guilt/empathy, shallow affect, and the callous and manipulative use of others. Individuals showing CU traits have increased risk for behavior problems and reduced responses to displays of distress in others. To explore how deficits in emotion-processing are associated with CU traits, the current study examined the association between callous-unemotionality and a neural index of facial emotion processing, using the event-related potential techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
(94 reference statements)
0
10
1
Order By: Relevance
“…It is possible that age influences N170 amplitude in a non-linear manner. The study by Hoyniak et al (2019) with the youngest age group of children aged three to five years found significant age effects, whereby the N170 became larger with age. Rather than continuing to become larger with age, studies with older children sometimes found effects in the opposite direction.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…It is possible that age influences N170 amplitude in a non-linear manner. The study by Hoyniak et al (2019) with the youngest age group of children aged three to five years found significant age effects, whereby the N170 became larger with age. Rather than continuing to become larger with age, studies with older children sometimes found effects in the opposite direction.…”
Section: Resultsmentioning
confidence: 92%
“…Six studies investigated the relationship between N170 amplitude and age during early-to-middle childhood (see Table 2 ). Three studies reported significant age effects, however two studies reported that N170 amplitude became weaker (i.e., less negative) with increasing age ( Batty and Taylor, 2006 ; Meaux et al;, 2014 ), while one study found N170 amplitude became stronger (i.e., more negative) with age ( Hoyniak et al, 2019 ). The remaining three studies ( Battaglia et al, 2007 ; Chronaki et al, 2018 ; Miki et al, 2011 ) reported no meaningful changes in N170 amplitude with age.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It should also be noted that fear—but not happiness, sadness, and anger—recognition showed significant main and interactive relations to ethical guilt. This aligns with studies documenting fear‐specific processing deficits in children who have difficulties feeling guilt (e.g., Hoyniak et al ., ). Guilt often revolves around actions that intend harm.…”
Section: Discussionmentioning
confidence: 97%
“…Most developmental studies concerning facial expression recognition and guilt consider relatively global callous‐unemotional (CU) traits. For example, children with higher CU traits took longer than controls to recognize increasingly sad facial expressions, were more likely to mistake fearful expressions for others (Blair, Colledge, Murray, & Mitchell, ), and showed blunted neural responses to fearful faces (Hoyniak et al ., ). However, the extent to which distress recognition factors into children's guilt per se remains unclear because CU traits include social‐emotional deficits beyond low guilt (e.g., low sympathy and low general affect; Frick, ).…”
Section: Introductionmentioning
confidence: 97%